Reduction in the risk of contrast-induced nephropathy using enhanced external counter-pulsation in patients with chronic kidney disease - Chun-Mei Zeng; Hong-Yu Pan; Yan-Mei Zhao; Zheng Ling; Ming Liu; Ying Feng (Renal Failure)
Objective To evaluate the efficacy of EECP in the prevention of contrast-induced nephropathy (CIN) in patients with chronic kidney disease (CKD).Methods A prospective trial was undertaken in the participants. A total of 280 patients with an estimated glomerular filtration rate (eGFR) of <60 ml/min/1.73 m2 who underwent percutaneous coronary artery procedures were enrolled and divided into two groups: the control group (n = 100) and the EECP group (n = 180). All patients received extracellular fluid volume expansion therapy with 0.9% normal saline, and patients in the EECP groups were also treated with EECP. The renal function indexes of the two groups were determined 48–72 h after coronary artery procedures.Results In the EECP group, the BUN and serum creatinine (Scr) after coronary artery procedures were significantly lower than those before coronary artery procedures (BUN: 8.4 ± 3.5 vs. 6.6 ± 2.7 mmol/L, p < 0.001; Scr: 151.9 ± 44.7 vs. 144.5 ± 48.3 μmol/L, p < 0.001), while the eGFR was significantly increased (43.6 ± 11.4 vs. 47.1 ± 13.9 ml/min/1.73 m2, p < 0.001). The degree of Scr elevation was lower in the EECP group than in the control group (12.4 ± 15.0 vs. 20.9 ± 24.8 μmol/L, p = 0.026). Additionally, the EECP group had a lower incidence of post-procedures Scr elevation than the control group (36.5 vs. 48.0%, p = 0.042), a higher incidence of post-procedures eGFR elevation (62.2 vs. 48.0%, p = 0.021), and a lower risk of CIN (1.1 vs. 6.0%, p = 0.019).Conclusion EECP therapy has a protective effect on renal function and can reduce the risk of CIN in patients with CKD.